Chronic Sclerosing Osteomyelitis of the Mandible Treated with Hemimandibulectomy and Fibular Free Flap Reconstruction. Issue 12 (December 2015) - Singh, Shubhi; Graham, M. Elise; Bullock, Martin; Rigby, M.H.; Taylor, S. Mark; Trites, Jonathan R.B.; Hart, Robert D.
Abstract : Summary: Primary chronic osteomyelitis of the mandible is a rare condition that presents with a long-standing chronic facial swelling over the mandible, pain with mastication, and trismus. With no clinically appreciated acute phase, the aetiology often remains unknown. Many patients achieve adequate symptom control with broad-spectrum antibiotics, hyperbaric oxygen therapy and surgical debridement, or decortication of bone sequestration. However, because of the rarity of primary chronic osteomyelitis and the extensive involvement of the mandible that can result, we present a case of a 32-year-old woman with chronic disease of the left mandible requiring a left hemimandibulectomy and fibular free flap reconstruction. Few such cases have been reported in the literature, which require such extensive resection and reconstruction to control long-standing symptoms.